Nitrate pollution in dairy farms and its impact on groundwater quality in a sector of the Pampas plain, Argentina - Cellone, Francisco Aldo (2020)
The aim of this work is to evaluate the nitrate content and its impact on groundwater quality used for supply in dairy farms in a sector of the Pampas Plain in relation to specific point sources of pollution. Samples were collected in nine dairy farms during the months of June, August and November 2017 and April 2018. In all the samples, electrical conductivity and pH were measured in situ with a portable multiparameter equipment and water samples were collected to determine nitrates content. In the April 2018 sampling, carbonates, bicarbonates, chlorides, sulphates, nitrates, sodium, calcium, magnesium, and potassium were also determined. Results show that groundwater is mainly sodium bicarbonate to magnesium calcium bicarbonate type with variable pH and salinity. Nitrates and hardness were above the limits for human and animal consumption. Nitrate contents are significantly correlated with pH, electrical conductivity and hardness, and tend to decrease in wells which are more distant from point sources of pollution. In turn, the incorporation of other ions into the aquifer is evidenced by the increase of chlorides and EC and their correlation with nitrates. It is interpreted that the nitrification process acidifies the medium, triggering the dissolution of carbonates present in the aquifer matrix which increases groundwater hardness. Water quality deterioration could not only put at risk farmers’ health but it also conditions animal production and the dairy farm machinery. This study is the first contribution to defining local guidelines to set a proper water management plan as well as to provide tools to address the problem in other dairy farms in this sector of the Pampas Plain and in other regions.